PEMANFAATAN TEKS PROSEDUR PADA MAJALAHMARKETEERS SEBAGAI BAHAN AJAR DALAM BENTUK LKPD - Ananti, Okyana Giti; Ariyani, Farida; Fuad, Muhammad (FKIP Universitas Lampung, 2020)
This research was aimed to describing the structure and linguistic features of a procedure text in Marketeers business magazine of June 2018,setting up the lesson plan of teaching procedure text, and creating the teaching material in form of students? worksheet related to procedure text for eleventh grade students of senior high school. This research was qualitative by using descriptive method in nature. The result of this research found out the structure and linguistic features of a procedure text in Marketeers business magazineof June 2018. The product results were the lesson plan and teaching materials in form of students' worksheet which were suitable with the material related to the procedure text for eleventh grade students of senior high school. Tujuan penelitian ini mendeskripsikan struktur dan kaidah kebahasaan teks prosedur pada majalah bisnis Marketeers edisi Juni 2018, membuat rencana pelaksanaan pembelajaran teks prosedur, danmerancang bahan ajar dalam bentuk LKPD teks prosedur untuk SMA kelas XI. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif.Hasil penelitian inimenemukan struktur dan kaidah kebahasaan teks prosedur pada majalah bisnis Marketeers edisi Juni 2018.Produk yang dihasilkan ialah rencana pelakasanaan pembelajaran dan bahan ajar dalam bentuk lembar kegiatan peserta didik yang cocok untuk pembelajaran teks prosedur Kelas XI SMA. Kata kunci: teks prosedur, rencana pelaksanaan pembelajaran, danlembar kegiatan peserta didik